Conceptualizing Spiritual Psychotherapy as a Nursing Intervention: A Concept Analysis - Lia Mulyati; Mekar Dwi Anggraeni; Arif Setyo Upoyo (Journal of Psychosocial Nursing and Mental Health Services, 2026)
Purpose: Spiritual psychotherapy has been increasingly used in nursing; however, conceptual diversity limits its consistent use in addressing psychological and spiritual distress. The current article presents a concept analysis of spiritual psychotherapy as a nursing intervention to define its attributes, antecedents, consequences, and operational meaning for psychosocial and spiritual nursing practice. Method: An international literature review was conducted using Walker and Avant's concept analysis to identify recurring psychospiritual patterns. Results: Five defining attributes were identified: guided meaning-making, therapeutic spiritual presence, activation of inner healing, mind–spirit integration, and a sacred therapeutic relationship. Antecedents included spiritual or existential distress, emotional vulnerability, spiritual readiness, a trusting nurse–patient relationship, supportive environments, and nurses' spiritual awareness. Conceptual consequences comprised enhanced spiritual well-being, emotional regulation, resilience, meaning reconstruction, and reduced existential distress. Conclusion: This clarification of spiritual care provides a conceptual foundation for psychosocial and mental health nursing practice, supporting its intentional integration into holistic nursing interventions.